Fukushima: The World’s Gravest Disaster in History: Molecular Mechanisms - Bustamante Pérez, José O. (Revista Universidad de Guayaquil, 2014)
On March 11, 2011, the greatest disaster in human history started in Fukushima. Youtube and other independent internet media maintain us informed on the increasing threat of Fukushima. Since my arrival in Ecuador on November 2012, I have been a taxi customer in Guayaquil: The Pearl of The Pacific, Ecuador’s biggest city. My work visa describes me as Investigator. Therefore, I have been faithful to this description. I arrive to the end of 2013 without finding a cab driver that knows the word Fukushima. Since my university studies (School of Physics, University of Havana) I have been interested in Nuclear Physics, Nuclear Reactors, etc. In 1972 I finished my studies and went to work for the Ministry of Public Health (Havana). Since 1972 I keep up with advances in Medical Physics (Radiotherapy, Radioprotection, Imaging, Defibrillation, Lasers, etc). Also in 1972 I started training as Biophysicist and Physiologist. In 1977 I defended my Doctoral thesis. In 1989 I started studying Cell and Molecular Biology. I have published in prestigious international journals such as: Science, Biophysical Journal, Physiological Reviews, etc. Here I emphasize our social and moral obligation of keeping updated and informing the public on Fukushima and how it impacts Ecuador.
Keywords: Radiotherapy; Radioprotection; Imaging; Defibrillation